Morphological alterations caused by manual venom extraction on the main venom gland of Bothrops asper and Crotalus simus snakes (Serpentes: Viperidae): Long-term implications for antivenom production - Rodríguez Abarca, Sylvia (2019)
Rodríguez, S. (2019). Morphological alterations caused by manual venom extraction on the main venom gland of Bothrops asper and Crotalus simus snakes (Serpentes: Viperidae): Long-term implications for antivenom production. [Tesis de Licenciatura]. Universidad Nacional, Heredia, Costa Rica. Proyecto final de Graduación presentado bajo la modalidad de artículo científico para optar por el grado de Licenciatura en Biología con énfasis en manejo de recursos naturales.